EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR AND SHARE (TPS) DAN TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) DENGAN PENDEKATAN SAINTIFIK PADA MATERI BANGUN RUANG SISI LENGKUNG DITINJAU DARI KECERDASAN SPASIAL - Virlina Zuhanisani; Budiyono Budiyono; Sri Subanti (Jurnal Pembelajaran Matematika, 2016)
Abstract: The purpose of this study was to determine the effect of the learning models on the learning achievement in Mathematics viewed from the spatial intelligence of the students. The learning models compared were the cooperative learning model of the Think Pair And Share (TPS) type with scientific approach, Team Assisted Individualization (TAI) model type with scientific approach, and classical model with scientific approach. The type of this study was a quasi-experimental study with a 3x3 factorial design. The population was all grade IX students of Junior High Schools in Grobogan Regency. Instruments used for data collection were mathematics achievement test and spatial intelligence test. Data analysis tecnique was used to test the hypothesis was  two-ways analysis of variance with unbalanced cell as a 3x3 factorial design. Based on the hypothesis, the results of the study can be explained as follows. (1) Scientific TPS got better achievement than scientific TAI and with scientific classical, scientific TAI got better achievement than scientific classical. (2) Students with high spatial intelligence got the same achievement as middle spatial intelligence. In addition, students who had high and middle spatial intelligence got better achievement than those who had low spatial intelligence. (3) In the spatial intelligence of high category, the achievement of the students who were treated with scientific TPS was better than those who were treated with scientific TAI and treated with scientific classical, students treated who were with scientific TAI got same achievement with those treated who were with scientific classical. In the spatial intelligence category of middle and low, with scientific TPS, with scientific TAI and with scientific classical gave the same achievement. (4) In the with scientific TPS, the students who had high spatial intelligence got the same achievement with middle spatial intelligence. In addition, the students who had high and middle spatial intelligence got better achievement than those who had low spatial intelligence. In the with scientific TAI and with scientific classical, the students who had high, middle, and low spatial intelligence got same achievement.Keywords: Think Pair And Share, Team Assisted Individualization, Classical, Scientific Approach, Spatial Intelligence.